It is currently 17 Oct 2017, 02:58

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# If (y+3)(y-1)-(y-2)(y-1)=r(y-1), what is the value of y?

Author Message
TAGS:

### Hide Tags

Intern
Joined: 21 Aug 2011
Posts: 23

Kudos [?]: 20 [0], given: 0

If (y+3)(y-1)-(y-2)(y-1)=r(y-1), what is the value of y? [#permalink]

### Show Tags

24 Aug 2011, 20:04
7
This post was
BOOKMARKED
00:00

Difficulty:

55% (hard)

Question Stats:

57% (01:15) correct 43% (01:21) wrong based on 150 sessions

### HideShow timer Statistics

If (y+3)(y-1)-(y-2)(y-1)=r(y-1), what is the value of y?

(1) r^2=25
(2) r=5
[Reveal] Spoiler: OA

Last edited by Bunuel on 13 May 2013, 03:20, edited 1 time in total.
Edited the question.

Kudos [?]: 20 [0], given: 0

Veritas Prep GMAT Instructor
Joined: 16 Oct 2010
Posts: 7668

Kudos [?]: 17324 [2], given: 232

Location: Pune, India

### Show Tags

24 Aug 2011, 23:23
2
KUDOS
Expert's post
1
This post was
BOOKMARKED
Jasonammex wrote:
if (y+3)(y-1)-(y-2)(y-1)=r(y-1), what is the value of y?

(1) r^2=25
(2) r=5

I chose A...

In the equation above we see that (y-1) is the common factor in all terms. So let's take (y-1) common out of all the terms.

(y+3)(y-1) - (y-2)(y-1) - r(y-1) = 0
(y-1)[(y+3) -(y-2) - r] = 0
(y-1)(5 - r) = 0

Now, the product of these two is 0. This means that at least one of them has to be 0.
Either (y-1) = 0 or (5 - r) = 0 or both are 0.
So, either y = 1 or r = 5 or both.
Only if we know that r is not 5, then we can say that y must be 1. If r is 5, y may be 1 or may not be 1.

Stmnt 1: r^2 = 25
So r = +- 5
This statement tells us that r can be 5.
If r = 5, y may or may not be 1.
If r is not 5, y will be 1.
Since we do not know whether r is 5 or not, we cannot say what the value of y is. Not sufficient.

Stmnt 2: r = 5
If r = 5, y may or may not be 1.
Not sufficient.

Both together, r = 5. Again, not sufficient. Answer E
_________________

Karishma
Veritas Prep | GMAT Instructor
My Blog

Get started with Veritas Prep GMAT On Demand for \$199

Veritas Prep Reviews

Kudos [?]: 17324 [2], given: 232

Director
Status: Finally Done. Admitted in Kellogg for 2015 intake
Joined: 25 Jun 2011
Posts: 535

Kudos [?]: 4110 [0], given: 217

Location: United Kingdom
GMAT 1: 730 Q49 V45
GPA: 2.9
WE: Information Technology (Consulting)

### Show Tags

26 Aug 2011, 02:49

y-1 is the common factor in the question stem

Try to break the stem as much as you can

So, y-1[(y+3) - (y-2)] = r(y-1)

= y+3-y+2 = r

r=5. So the question becomes is r=5?

Statement 1 gives us two solution + and _ 5 So insufficient

Statement 2 is sufficient because its same as our new question stem which is r=5.

Hope this helps.
_________________

Best Regards,
E.

MGMAT 1 --> 530
MGMAT 2--> 640
MGMAT 3 ---> 610
GMAT ==> 730

Kudos [?]: 4110 [0], given: 217

Director
Status: Finally Done. Admitted in Kellogg for 2015 intake
Joined: 25 Jun 2011
Posts: 535

Kudos [?]: 4110 [0], given: 217

Location: United Kingdom
GMAT 1: 730 Q49 V45
GPA: 2.9
WE: Information Technology (Consulting)

### Show Tags

26 Aug 2011, 02:50
I am wrong. Sorry guys. Thanks Karishma.
_________________

Best Regards,
E.

MGMAT 1 --> 530
MGMAT 2--> 640
MGMAT 3 ---> 610
GMAT ==> 730

Kudos [?]: 4110 [0], given: 217

Intern
Joined: 31 May 2010
Posts: 32

Kudos [?]: 2 [0], given: 2

### Show Tags

26 Aug 2011, 06:05
should be E.
The questions becomes y-1[y+3 - y+2)] = r(y-1).

r=5. So, can not calculate the value of Y from both 1 and 2.

Kudos [?]: 2 [0], given: 2

Manager
Joined: 29 Jul 2011
Posts: 104

Kudos [?]: 69 [0], given: 6

Location: United States
Re: if (y+3)(y-1)-(y-2)(y-1)=r(y-1), what is the value of y? (1) [#permalink]

### Show Tags

07 Jan 2012, 15:31
Rephrasing the stem provides us:

(y-1)[y+3-y+2] = r(y-1)
(y-1)5 = r(y-1)
(y-1)(5-r) = 0
y = 1 or r = 5

1. r = +/- 5, if r = -5, y = 1 and if r = 5, y = anything. Insuff.
2. r = 5, which means y = anything. Insuff.

Combined, only thing common is r = 5, which still provides y = anything. Insuff.

E.
_________________

I am the master of my fate. I am the captain of my soul.
Please consider giving +1 Kudos if deserved!

DS - If negative answer only, still sufficient. No need to find exact solution.
PS - Always look at the answers first
CR - Read the question stem first, hunt for conclusion
SC - Meaning first, Grammar second
RC - Mentally connect paragraphs as you proceed. Short = 2min, Long = 3-4 min

Kudos [?]: 69 [0], given: 6

Senior Manager
Joined: 25 Feb 2010
Posts: 450

Kudos [?]: 109 [0], given: 10

Re: if (y+3)(y-1)-(y-2)(y-1)=r(y-1), what is the value of y? (1) [#permalink]

### Show Tags

13 May 2013, 03:18
Guys I'm bit lost here.

(y-1)[y+3-y+2] = r(y-1)
(y-1)5 = r(y-1)

(y-1) is common here

so 5= r

which is what stmt 2 tells us.

I think i should be B.
_________________

GGG (Gym / GMAT / Girl) -- Be Serious

Its your duty to post OA afterwards; some one must be waiting for that...

Kudos [?]: 109 [0], given: 10

Math Expert
Joined: 02 Sep 2009
Posts: 41871

Kudos [?]: 128511 [1], given: 12179

Re: if (y+3)(y-1)-(y-2)(y-1)=r(y-1), what is the value of y? (1) [#permalink]

### Show Tags

13 May 2013, 03:30
1
KUDOS
Expert's post
onedayill wrote:
Guys I'm bit lost here.

(y-1)[y+3-y+2] = r(y-1)
(y-1)5 = r(y-1)

(y-1) is common here

so 5= r

which is what stmt 2 tells us.

I think i should be B.

Notice that we are asked to find the value of y not r. Also, I guess you reduced (y-1)5 = r(y-1) by y-1 which cannot be done here.

Never reduce an equation by a variable (or expression with a variable), if you are not certain that the variable (or the expression with a variable) doesn't equal to zero. We can not divide by zero.

So, if you divide (reduce) (y-1)5 = r(y-1) by y-1, you assume, with no ground for it, that y-1 does not equal to zero thus exclude a possible solution (notice that both y=1 AND r=5 satisfy the equation).

Hope it's clear.

Complete solution:

If (y+3)(y-1)-(y-2)(y-1)=r(y-1), what is the value of y?

$$(y+3)(y-1) - (y-2)(y-1) - r(y-1) = 0$$ --> $$(y-1)[(y+3) -(y-2) - r] = 0$$ --> $$(y-1)(5 - r) = 0$$ --> y=1 or/and r=5.

(1) r^2=25 --> r=5 or r=-5. Not sufficient.
(2) r=5 --> y may or may not be 1. Not sufficient.

(1)+(2) The same here: we have that r=5 but y still may or may not be 1. Not sufficient.

_________________

Kudos [?]: 128511 [1], given: 12179

Manager
Status: Working hard to score better on GMAT
Joined: 02 Oct 2012
Posts: 89

Kudos [?]: 190 [0], given: 23

Location: Nepal
Concentration: Finance, Entrepreneurship
GPA: 3.83
WE: Accounting (Consulting)
Re: If (y+3)(y-1)-(y-2)(y-1)=r(y-1), what is the value of y? [#permalink]

### Show Tags

14 May 2013, 21:21
Hi Buneul, has my logic actually worked here?
correct me if i am wrong...
Jasonammex wrote:
If (y+3)(y-1)-(y-2)(y-1)=r(y-1), what is the value of y?

(1) r^2=25
(2) r=5

From the given statement:
(y-1)[Y+3-y+2]=r(y-1)
Divide both sides by (y-1)

y+3-y+2=r
r=5

Here I thought that in the given statement when Y does not exist it is impossible to calculate the value of Y.
Thus both statements are not sufficient.
Ans: E
_________________

Do not forget to hit the Kudos button on your left if you find my post helpful.

Kudos [?]: 190 [0], given: 23

Math Expert
Joined: 02 Sep 2009
Posts: 41871

Kudos [?]: 128511 [0], given: 12179

Re: If (y+3)(y-1)-(y-2)(y-1)=r(y-1), what is the value of y? [#permalink]

### Show Tags

15 May 2013, 01:53
atalpanditgmat wrote:
Hi Buneul, has my logic actually worked here?
correct me if i am wrong...
Jasonammex wrote:
If (y+3)(y-1)-(y-2)(y-1)=r(y-1), what is the value of y?

(1) r^2=25
(2) r=5

From the given statement:
(y-1)[Y+3-y+2]=r(y-1)
Divide both sides by (y-1)

y+3-y+2=r
r=5

Here I thought that in the given statement when Y does not exist it is impossible to calculate the value of Y.
Thus both statements are not sufficient.
Ans: E

Unfortunately that's not correct. Refer to my post above: if-y-3-y-1-y-2-y-1-r-y-1-what-is-the-value-of-y-119561.html#p1224280

Never reduce an equation by a variable (or expression with a variable), if you are not certain that the variable (or the expression with a variable) doesn't equal to zero. We can not divide by zero.

So, if you divide (reduce) (y-1)5 = r(y-1) by y-1, you assume, with no ground for it, that y-1 does not equal to zero thus exclude a possible solution (notice that both y=1 AND r=5 satisfy the equation).
_________________

Kudos [?]: 128511 [0], given: 12179

Manager
Status: Working hard to score better on GMAT
Joined: 02 Oct 2012
Posts: 89

Kudos [?]: 190 [0], given: 23

Location: Nepal
Concentration: Finance, Entrepreneurship
GPA: 3.83
WE: Accounting (Consulting)
Re: If (y+3)(y-1)-(y-2)(y-1)=r(y-1), what is the value of y? [#permalink]

### Show Tags

15 May 2013, 21:11
_________________

Do not forget to hit the Kudos button on your left if you find my post helpful.

Kudos [?]: 190 [0], given: 23

GMAT Club Legend
Joined: 09 Sep 2013
Posts: 16764

Kudos [?]: 273 [0], given: 0

Re: If (y+3)(y-1)-(y-2)(y-1)=r(y-1), what is the value of y? [#permalink]

### Show Tags

22 May 2016, 09:59
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________

Kudos [?]: 273 [0], given: 0

Director
Joined: 18 Oct 2014
Posts: 906

Kudos [?]: 410 [0], given: 69

Location: United States
GMAT 1: 660 Q49 V31
GPA: 3.98
Re: If (y+3)(y-1)-(y-2)(y-1)=r(y-1), what is the value of y? [#permalink]

### Show Tags

22 May 2016, 11:41
Jasonammex wrote:
If (y+3)(y-1)-(y-2)(y-1)=r(y-1), what is the value of y?

(1) r^2=25
(2) r=5

Given information=
(y+3)(y-1)-(y-2)(y-1)=r(y-1)

Question- value of y?

Inference from given information-

(y+3)(y-1)-(y-2)(y-1)=r(y-1)
(y+3)- (y-2)= r (y-1) is common at both the sides of the equation.
y+3-y+2=r
r=5
(y is cancelling out at both sides of equation, so most likely we need one of the statement to produce value of y )

(1) r^2=25
It does not give us a solution for y

(2) r=5
It does not give us a solution for y

_________________

I welcome critical analysis of my post!! That will help me reach 700+

Kudos [?]: 410 [0], given: 69

GMAT Club Legend
Joined: 09 Sep 2013
Posts: 16764

Kudos [?]: 273 [0], given: 0

Re: If (y+3)(y-1)-(y-2)(y-1)=r(y-1), what is the value of y? [#permalink]

### Show Tags

22 May 2017, 20:08
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________

Kudos [?]: 273 [0], given: 0

Re: If (y+3)(y-1)-(y-2)(y-1)=r(y-1), what is the value of y?   [#permalink] 22 May 2017, 20:08
Display posts from previous: Sort by